2020
DOI: 10.1002/er.5088
|View full text |Cite
|
Sign up to set email alerts
|

The special route toward conversion of methane to methanol on a fluffy metal‐free carbon nitride photocatalyst in the presence of H 2 O 2

Abstract: Summary A fluffy mesoporous graphitic carbon nitride (g‐CN) was synthesized and investigated, as the first metal‐free polymeric semiconductor photocatalyst, for partial oxidation of methane to methanol at a mild condition (35°C) in the presence of hydrogen peroxide (H2O2). The addition of g‐CN photocatalyst enhanced the methanol production with H2O2 by 10 times under visible light and this production was 3‐folds that when WO3 was used. Besides, while attaining a comparable saturated production of CH3OH, the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 54 publications
(144 reference statements)
0
55
0
Order By: Relevance
“…[20][21][22] Previous works have demonstrated that such properties strongly influence the oxidation of methane. [23][24][25] For instance, a comparison of the photocatalytic performance of materials from each category (TiO 2 , NiO, and WO 3 ) shows that the latter exhibited a higher methanol selectivity. [23] The maximum conversion rates of methane to methanol over WO 3 , TiO 2 , and NiO were 29 %, 21 %, and 20 %, respectively.…”
Section: Mechanism Of the Photocatalytic Conversion Of Methane Into Methanolmentioning
confidence: 99%
See 3 more Smart Citations
“…[20][21][22] Previous works have demonstrated that such properties strongly influence the oxidation of methane. [23][24][25] For instance, a comparison of the photocatalytic performance of materials from each category (TiO 2 , NiO, and WO 3 ) shows that the latter exhibited a higher methanol selectivity. [23] The maximum conversion rates of methane to methanol over WO 3 , TiO 2 , and NiO were 29 %, 21 %, and 20 %, respectively.…”
Section: Mechanism Of the Photocatalytic Conversion Of Methane Into Methanolmentioning
confidence: 99%
“…For instance, Shi et al studied the performance of a C 3 N 4 photocatalyst in the selective oxidation of methane, finding that this material can only generate methanol in the presence of H 2 O 2 . [25] To better elucidate the reaction mechanisms, the authors used three radical scavengers to identify the role of h + , O �À 2 , and HO * radicals. Unlike previous works, the results indicated that the photogenerated holes along with the superoxide radical also contribute to the generation of methanol [Eqs.…”
Section: Mechanism Of the Photocatalytic Conversion Of Methane Into Methanolmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Xiao et al reported an AuPd@ZSM‐5 catalyst for methane oxidation by in situ generated H 2 O 2 at a mild temperature (70°C), and the methanol productivity was up to 91.6 mmol/g AuPd ∙h 17 . Also, our group have reported that graphitic carbon nitride as metal‐free photocatalyst was effective for the conversion of methane to methanol at 35°C in the presence of H 2 O 2 , and the methanol production was promoted by ~10 times under visible light 24 …”
Section: Introductionmentioning
confidence: 99%